A new species of the genus Dendarus Dejean, 1821 from Southwest Iran (Coleoptera: Tenebrionidae: Dendarini) - Mofrad, Farhad Eshraghi (Zootaxa, 2024)
A new tenebrionid species of the genus Dendarus Dejean, 1821, Dendarus (Pandarinus) nabozhenkoi sp. n. is described from Chaharmahal and Bakhtiari Province, Iran. Dendarus nabozhenkoi sp. n. is most similar to Dendarus matthewsi Nabozhenko, 2022 and Dendarus simplex Seidlitz, 1893 differing in the shape of the pronotum, the structure of the male pro- and metatibiae, the reduced goldish hair brush on the sole surface of mesotarsomere 2 and the structure of the aedeagus and spiculum gastrale.